JENIS BAKTERI DAN SENSITIVITAS ANTIBIOTIK PADA KASUS INFEKSI NOSOKOMIAL AKIBAT PEMASANGAN KATETER DI RSSA MALANGDALAM PERIODE NOVEMBER 2000 - MARET 2001 - Djunaedi, Djoni (Fakultas Kedokteran Universitas Brawijaya, 2006)
The incidence of Nosocomial Infection (NI) includinginfection of the urinary tract attributable to catheter insertion aggravates the existing conditions. Local symptoms and septis that occured could prolong hopitalization, and even caused death. So far, prevention of NI has been undertaken only through the adherence to the standard procedure. The important problem that arises is whether the prevention of NI should rely only on the adherence of thestandard procedure. In order to find the solution, an appropriate investigation is called for. The materials utilized were (a) urine collected from obstetric-gynaecological patients that required catheter insertion – urine sample was taken using antiseptical procedures before and after catheter insertion within the period of 2x24 hours, (b) the end section of catheter canule when the the catheter was taken off. The materials were cultured in blood plates. Bacterial counts were performed on the data with respect to bacterial types and their sensitivity to antibiotics of the families of Cephalosporin (Cefotaxim), Aminoglycoside (Amikacin), Quinolone (Ciprofoxacine), Penicilline (Amoxicilline, Ampicilline), cotrimoxazole and Nitrofurantoin.